The influence of noise in vehicles on the driver’s subjective evaluation of driveability - Wi, Hyoseong; Park, Jinil; Lee, Jonghwa (Proceedings of the Institution of Mechanical Engineers, Part D: Journal of Automobile Engineering, 2018)
Driveability, including maneuverability, stability, and riding quality, is one of the most important factors determining the marketability of vehicles. However, unlike fuel economy or engine performance, driveability is very difficult to be evaluated quantitatively. With regard to research on vehicle noise related to driveability, existing works mainly deal with quantification or improvement methods. In this study, the various physical quantities regarding vehicle operating conditions were measured and the noise characteristics were manipulated in several ways to evaluate and analyze the influence of noise on subjective drivability. The results show that the noise level as well as noise frequency characteristics are influencing the drivers’ subjective evaluation of driveability.
Keywords: Driveability; frequency; Noise characteristic; Physical quantities; sensibility evaluation; Subjective evaluations; Vehicle noise; Vehicle operating conditions; Driveability; frequency; riding quality; sensibility evaluation; vehicle noise